1984
DOI: 10.1073/pnas.81.14.4343
|View full text |Cite
|
Sign up to set email alerts
|

Catalase: a tetrameric enzyme with four tightly bound molecules of NADPH.

Abstract: Catalases (H202:H202 oxidoreductase, EC 1.11.1.6) from many species are known to be tetramers of 60,000-dalton subunits, with four heme groups per tetramer. Previous authors have determined the amino acid sequence and three-dimensional structure of bovine liver catalase. Studies of the regulation of the pentose phosphate pathway led the present authors to a search for proteins that bind NADP+ and NADPH in human erythrocytes. An unexpected result of that search was the finding that a major reservoir of bound NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
249
2
4

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(267 citation statements)
references
References 19 publications
12
249
2
4
Order By: Relevance
“…Indeed, it has been reported that CAT and GPXs can be inactivated by oxidative attack. 55,56 In this report, using LECs derived from mice with targeted inactivation of PRDX6, we show that PRDX6-deficient LECs display phenotypic changes, spontaneous apoptosis, and enhanced expression of a-SM actin (a bio-marker for cataractogenesis). These changes of Prdx6 À/À LECs are indistinguishable from those of TGFb-induced changes in LECs.…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, it has been reported that CAT and GPXs can be inactivated by oxidative attack. 55,56 In this report, using LECs derived from mice with targeted inactivation of PRDX6, we show that PRDX6-deficient LECs display phenotypic changes, spontaneous apoptosis, and enhanced expression of a-SM actin (a bio-marker for cataractogenesis). These changes of Prdx6 À/À LECs are indistinguishable from those of TGFb-induced changes in LECs.…”
Section: Discussionmentioning
confidence: 75%
“…CAT activity has been associated with UVR response of freshwater cladocerans to harmful photochemicals such as H 2 O 2 and free radicals (Barata et al 2005). In addition, CAT contains four tightly bound molecules of reduced nicotinamide adenine dinucleotide phosphate (NADPH), and, although this dinucleotide is not essential for enzyme activity, its presence decreases the susceptibility of the enzyme to be inactivated when exposed to H 2 O 2 (Kirkman and Gaetani 1984). NADPH is generated mostly in the pentose phosphate pathway (PPP), an alternative Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is much conflicting evidence in the literature, however, regarding the relative contributions of these enzymes to this process in eutherian RBC (Cohen and Hochstein, 1963;Kirkman and Gaetani, 1984;Gaetani et al, 1989). To our knowledge, the actual relation-ship between GSH-Px and catalase activities has not been investigated until now.…”
Section: Relationship Between Gsh-px and Catalasementioning
confidence: 99%